Dilution in Director Risk Assessments: The Effects of Diagnostic and Non-diagnostic Information - SEOW, Jean Lin (Institutional Knowledge at Singapore Management University, 2013)
This paper reports the results of an experiment investigating how directors’ identification and evaluation of diagnostic and non-diagnostic information in a financial statement fraud risk assessment setting affects dilution in their risk assessments. My results show that more (less) diluted risk assessments are made when more (fewer) nondiagnostic factors are identified and where less (more) weight is placed on non-diagnostic factors identified as relevant to the judgment decision. Directors with higher levels of technical knowledge are found to identify more diagnostic factors and place greater weight on these factors than directors with lower levels of technical knowledge. Higher levels of technical knowledge are also associated with marginally lower weights placed on nondiagnostic factors and a resultant lower susceptibility to dilution in judgment decisions. Audit committee members with higher levels of technical knowledge are also found to make less diluted risk assessments. Directors who possess lower levels of technical knowledge are found to be unable to bridge the ‘gap’ in their performance compared to directors with higher technical knowledge even with the assistance of a decision aid. Collectively, these findings indicate that technical knowledge is a key driver in the ability of directors to identify and evaluate risk factors, and that any lack of technical knowledge may not easily be supplemented with decision aids. The findings also suggest that some commonly-used measures of director task expertise and competence may be inappropriate proxies for their risk assessment capabilities.